Role of the intestine in the pathogenesis of sepsis and organ multisystem failure - Peyroulou Cagnone, Alfredo (Cirugía del Uruguay, 1992)
Mu/tiple organ fai/ure (MOF) tend to be the most common cause of death of grave/y injured patients. lts existence is linked to sepsis and, according to some authors, is a synonim of sepsis. However, a great group of these patients does not have demonstrated bacteriological focus or positive hemocu/tures. A/so, the in tes ti ne of these patients is general/y grave/y affected by splacnic ischemia and constitutes a «reservoir» for resistan/ pathogen germs. The following hypothesis seems reasonable: linking the persistance of mu/tiple organ failure to an altera/ion of the «barrier» function of the intestine with «translocation» of germs and toxins to mesentheric lymph nades, blood stream. and perifonea/ cavity.